2018
DOI: 10.1038/s41589-018-0025-4
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of a ClC chloride transporter retains memory of its evolutionary history

Abstract: ClC chloride channels and transporters are important for chloride homeostasis in species from bacteria to human. Mutations in ClC proteins cause genetically inherited diseases, some of which are likely to have folding defects. The ClC proteins present a challenging and unusual biological folding problem because they are large membrane proteins possessing a complex architecture with many re-entrant helices that go only part way through membrane and loop back out. Here we were able to examine the unfolding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 60 publications
1
53
0
Order By: Relevance
“…In addition, 3/4TMH protodomains provide cohesive energetically stable supersecondary structural units that can self-assemble. The biophysical evidence is only now beginning to emerge (Min et al 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 3/4TMH protodomains provide cohesive energetically stable supersecondary structural units that can self-assemble. The biophysical evidence is only now beginning to emerge (Min et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The latter could in fact be described as a pseudo-quaternary organization of protodomains (Myers-Turnbull et al 2014;Youkharibache 2019). A recent biophysical study on the ClC chloride transporter found that the transporter is made up of two halves that fold independently as stable subunits, suggesting an evolutionary history of a stable protodomain that duplicated (Min et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Note that forces become negative values when a certain terminal COM moves more than a target position (defined by the dummy point) due to the thermal fluctuation. This could be considered to be evidence that the pulling speed in this work is low enough to probe a realistic response (although a pulling speed of 500 mm/s in this study is still much higher than those used in experiments whose usual highest pulling speed reaches 0.01 mm/s in atomic force microscopy 36 , 37 , or at most 0.1 mm/s 38 ).
Figure 5 Force profiles as a function of D EE for different systems, ( A ) (red) and (blue) and ( B ) (green) and (black).
…”
Section: Resultsmentioning
confidence: 82%
“…Since the publication of the force spectroscopy experiments on GlpG 3 , the same method has been applied to a designed α -helical transmembrane protein with four transmembrane helices 5 and a large chloride transporter, ClC, that has a complex topology and two independently metastable subdomains 4 . In the case of the designed transmembrane protein, unfolding occurs cooperatively in a single step and refolding after force-induced unfolding was found to be reliable and to occur in two steps.…”
Section: Discussionmentioning
confidence: 99%